Experimental Measurements to Study Correlations between Porosity, Absolute Permeability, and Capillary Pressure - Mahmud, Walid M.; Jaluta, Adel M. (International Journal of Petroleum Technology, 2023)
Rock permeability is a measurement of how easily a fluid can flow through a rock while porosity is a measure of the rock’s storage capacity or its pore volume that is capable of holding fluids. In many cases correlations may exist between porosity and permeability, however, these correlations are usually derived for a certain formation, and therefore they do not exhibit general application or validity. Cross-plot of permeability versus porosity data, to create a porosity-permeability transform, is sometimes used to assign permeability values to areas of a reservoir where permeability data are unavailable. The capillary pressure curve is also used to predict rock absolute permeability. In the present work, porosity, absolute permeability, and capillary pressure were measured experimentally to investigate and establish new correlations between porosity, Klinkenberg-corrected permeability, and capillary pressure. Fifty-nine core plugs, obtained from two different fields located in Sirte basin, Libya, were utilized. Results indicate that porosity might be a reasonable estimator of permeability, as correlations between porosity and permeability were observed and empirical permeability equations based on porosity were established. Capillary pressure was observed to be overall inversely proportional to permeability, however, determined capillary pressure curves varied within the same formation.